Peranan Rumah Budaya Sukuraga dalam menjaga eksistensi kesenian wayang Sukuraga khas Kota Sukabumi tahun 2016-2021 - Eva Nikmatul Rizky (Historiography: Journal of Indonesian History and Education, 2022)
This study aims to determine the factors causing the Sukuraga Cultural House to play a role in maintaining the existence of the Sukuraga Puppet art in 2016-2021, the role of the Sukuraga Cultural House in maintaining the existence of the Sukuraga Puppet art in 2016-2021, the implications of the role of the Sukuraga Cultural House, and the influence of the Sukuraga Cultural House for the community. This problem will be studied using the historical method assisted by the theory of cultural semiotics and modernization theory. The results of this study indicate that the existence of the Sukuraga Cultural House cannot be separated from the existence of the Sukuraga Puppet in Sukabumi. The main purpose of establishing the Sukuraga Cultural House is to maintain and improve the existence of the Sukuraga Puppet as well as a forum to shape the nation's character. The role of the Sukuraga Cultural House has fostered a creative economy. Puppet Sukuraga also became widely known by the public. Therefore, the presence of the Sukuraga Cultural House is very important for the community.Penelitian ini bertujuan untuk mengetahui faktor penyebab Rumah Budaya berperan dalam menjaga eksistensi kesenian Wayang Sukuraga tahun 2016-2021, peranan Rumah Budaya Sukuraga dalam menjaga eksistensi kesenian Wayang Sukuraga tahun 2016-2021, implikasi dari berperannya Rumah Budaya Sukuraga, dan pengaruh Rumah Budaya Sukuraga bagi masyarakat. Permasalahan itu akan dikaji dengan metode sejarah yang dibantu oleh teori semiotika budaya dan teori modernisasi. Hasil dari penelitian ini menunjukkan bahwa keberadaan Rumah Budaya Sukuraga tidak terlepas dari keberadaan Wayang Sukuraga di Sukabumi. Tujuan utama didirikannya Rumah Budaya Sukuraga adalah untuk mempertahankan dan meningkatkan eksistensi Wayang Sukuraga serta sebagai wadah untuk membentuk karakter bangsa. Berperannya Rumah Budaya Sukuraga telah menumbuhkan ekonomi kreatif. Wayang Sukuraga juga menjadi dikenal luas oleh masyarakat. Oleh karena itu, kehadiran Rumah Budaya Sukuraga sangat penting bagi masyarakat.